Within-tree carbon concentration variation in three Mexican pine species - Hernández Vera, Diego; Pompa García, Marín; Yerena Yamallel, José Israel; Alanís Rodríguez, Eduardo (2017)
SUMMARY Assessing carbon content in forest species is considered essential for programs designed to mitigate global warming. A value of 50 % has been assumed as a generic percentage. However, recent research indicates that there are substantial variations in carbon concentration even within a tree or tissues. The aim of this study was to assess the variations of carbon concentration along the longitudinal profile of Pinus durangensis, P. engelmannii and P. leiophylla in northern Mexico, including its components: root, bark, stem, branches, twigs, leaves and fruits. Using a selective sampling design, dominant and well-shaped trees were selected, whose samples were processed by chemical analyses. Results indicated significant differences in the mean concentration of carbon along the longitudinal profile, with the maximum value always at the base of the tree. Variations at the species level were also recorded. Pinus engelmannii had the lowest percentage with 49.31 %, followed by P. leiophylla (50.18 %) and P. durangensis (50.36 %). In the components of all species, the carbon concentration in the bark was higher than in the rest (52.48 %). A wide range of variation was observed in the carbon coefficients of the components of the species, from 47.39 % in the root of P. engelmannii to 53.49 % in the bark of P. leiophylla. It is therefore appropriate to consider these variations when making more accurate estimates of carbon stocks in forest ecosystems. Key words: Pinus durangensis, Pinus engelmannii, Pinus leiophylla, components, trees.